Establishment of a human iPSC line (MUSIi007-A) from peripheral blood of normal individual using Sendai viral vectors - Potirat, Ponthip; Wattanapanitch, Methichit; Kheolamai, Pakpoom; Issaragrisil, Surapol (Stem cell research, 2018)
Human induced pluripotent stem cell (iPSC) line was generated from peripheral blood mononuclear cells (PBMNCs) isolated from a 26-year-old healthy subject to use as a control group for the iPSC line carrying compound heterozygote for mutation in KLF1 gene. The cells were reprogrammed using integration-free method, Sendai viral (SeV) vectors containing KOS, hc-MYC and hKLF4. The established iPSC line (MUSIi007-A) exhibited a normal karyotype, expressed pluripotent markers and displayed in vitro and in vivo differentiation potential into cells of three embryonic germ layers. Resource tableUnlabelled TableUnique stem cell line identifierMUSIi007-AAlternative name(s) of stem cell lineSeV-iPSCInstitutionSiriraj Center of Excellence for Stem Cell Research,Faculty of Medicine Siriraj Hospital, Mahidol UniversityContact information of distributorPonthip Potirat, ponthip.pot@gmail.comSurapol Issaragrisil, surapolsi@gmail.comType of cell lineiPSCsOriginHumanAdditional origin infoAge: 26-year-oldSex: MaleEthnicity: ThaiCell sourcePeripheral blood mononuclear cellsClonalityClonalMethod of reprogrammingIntegration-free Sendai viral vectorsGenetic modificationN/AType of modificationN/AAssociated diseaseN/AGene/locusN/AMethod of modificationN/AName of transgene or resistanceN/AInducible/constitutive systemN/ADate archived/stock dateDecember 2014Cell line repository/bankN/AEthical approvalSiriraj Institutional Review Board (SiRB), no. Si248/2011, Faculty of Medicine Siriraj Hospital, Mahidol University, Thailand.